Occurrence characteristics, development status, and prospect of deep high-temperature geothermal resources in China - Rui CAO; Ji DOR; Yu-bin LI; Hui-ren MENG; Yong-qiang CAI (工程科学学报, 2022)
The geothermal resource has some advantages in energy-saving and emission-reduction. They include enormous reserves, high energy utilization efficiency, and low-cost operation and have played an important role in achieving the targets of carbon peak and carbon neutrality as the only renewable-clean energy on the planet that is not affected by weather and seasons. A systematical analysis of the developing courses and new progress of foreign countries’ middle-deep high-temperature geothermal resources was carried out to analyze the occurrence characteristics and development status of high-temperature geothermal resources. Furthermore, in comparison to the development of high-temperature geothermal resources in China, several suggestions which may provide a reference for the utilization of middle-deep geothermal resources in China are put forward for the actual demands. Conventional hydrothermal geothermal resources in China generally have mature power technology and significant potential. However, in comparison to the total resources, geothermal resources in China have a low development degree and significant development potential. Significantly, a variety of rare mineral resources are associated with geothermal fluids in China, but some issues exist in the development of the associated mineral resources in high-temperature geothermal fluids, such as unclear trace element distribution and development potential, resulting in a low level of resource development. Consequently, based on the potential evaluation of the associated mineral resources, comprehensive utilization of the associated mineral resources in deep geothermal fluids should be strengthened. High-temperature heat harm has become a significant problem as engineering construction in the high-temperature geothermal area has advanced, and the mining depth of mineral resources has gradually increased. The high-temperature heat harm not only has a serious impact on the health of workers but also impedes the construction process and raises costs. However, the resource attribute of high-temperature heat harm, on the other hand, has received little attention. Hence, there is relatively little research on the “resource utilization of heat energy” in deep mines and engineering construction, resulting in the waste of geothermal resources. Based on the potential evaluation of “heat harm resources,” more attention should be paid to the utilization of “heat harm resources” in engineering construction and “ore-thermal co-mining” in deep mines, as well as actively developing high-temperature heat harm resource utilization technology. In general, more attention should be paid to the development of China’s middle-depth geothermal resources. The development of an enhanced geothermal system based on conventional hydrothermal geothermal resources could be more effective. Furthermore, geothermal resource utilization should not be limited to geothermal fluid; associated mineral resources and high-temperature heat-harm resources have enormous resource potential as well.